2015
DOI: 10.1002/iub.1346
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of APC and RARβ2 genes in breast cancer patients

Abstract: Changes in the status of DNA methylation are one of the most common molecular alterations in human neoplasia. We aimed to identify epigenetic molecular markers in serum for early detection of breast cancer. Authors analyzed retrospectively the methylation status of RARb 2 and APC genes in serum samples from 121 breast cancer patients, 79 patients with benign breast diseases, and 66 healthy volunteers using methylationspecific PCR. The methylated APC and RARb 2 were significantly higher in breast cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Studies by Zmetakova I et al and Brooks JD et al reported no significant differences in methylation of APC between cases and controls.Zmetakova I, 2013 [42]PlasmaPyrosequencing (mean ± SD)34/5041–90/20–784.41 ± 7.812.53 ± 1.560.06Radpour R, 2011 [47]PlasmaEpiTyper assay (mean)36/3067/na0.39 b 0.19 b <0.0001Brooks JD, 2010 [56] d SerumQMSP (%)49/9652/51.824.2>0.05Hoque M, 2006 [44]PlasmaQMSP (%)47/3844.9/37.31700.008Van der Auwera I, 2009 [52]SerumQMSP (%)79/1962/392950.03Dulaimi E, 2004 [50]SerumMSP (%)34/2057.4/57.4290<0.05 c ESR1 Zmetakova I, 2013 [42]PlasmaPyrosequencing (mean ± SD)34/5041–90/20–784.18 ± 4.075.24 ± 4.330.338Only one study (Matinez-Galan, J) reported higher methylation levels of ESR1 in BC patients. Others observed no significant methylation differences.Zurita M, 2010 [54]SerumQMSP (%)77/34na/na0.005 b 0.085 b >0.05Van der Auwera I, 2009 [52]SerumQMSP (%)79/1962/392010.50.33Martinez-Galan J, 2008 [51]SerumMSP (%)106/7458/420.11 b 0.02 b 0.011 RARB Swellam M, 2015 [59]SerumMS-PCR (%)121/6643/4095.90<0.0001Higher frequency of methylated RARB was observed except the study conducted by Brooks JD et alBrooks JD, 2010 [56…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by Zmetakova I et al and Brooks JD et al reported no significant differences in methylation of APC between cases and controls.Zmetakova I, 2013 [42]PlasmaPyrosequencing (mean ± SD)34/5041–90/20–784.41 ± 7.812.53 ± 1.560.06Radpour R, 2011 [47]PlasmaEpiTyper assay (mean)36/3067/na0.39 b 0.19 b <0.0001Brooks JD, 2010 [56] d SerumQMSP (%)49/9652/51.824.2>0.05Hoque M, 2006 [44]PlasmaQMSP (%)47/3844.9/37.31700.008Van der Auwera I, 2009 [52]SerumQMSP (%)79/1962/392950.03Dulaimi E, 2004 [50]SerumMSP (%)34/2057.4/57.4290<0.05 c ESR1 Zmetakova I, 2013 [42]PlasmaPyrosequencing (mean ± SD)34/5041–90/20–784.18 ± 4.075.24 ± 4.330.338Only one study (Matinez-Galan, J) reported higher methylation levels of ESR1 in BC patients. Others observed no significant methylation differences.Zurita M, 2010 [54]SerumQMSP (%)77/34na/na0.005 b 0.085 b >0.05Van der Auwera I, 2009 [52]SerumQMSP (%)79/1962/392010.50.33Martinez-Galan J, 2008 [51]SerumMSP (%)106/7458/420.11 b 0.02 b 0.011 RARB Swellam M, 2015 [59]SerumMS-PCR (%)121/6643/4095.90<0.0001Higher frequency of methylated RARB was observed except the study conducted by Brooks JD et alBrooks JD, 2010 [56…”
Section: Resultsmentioning
confidence: 99%
“…With ten studies, RASSF1A was the most frequently evaluated gene and eight of them reported higher frequency of methylated RASSF1A in BC patients compared to controls [42, 4446, 50, 52, 5558]. APC has been investigated in seven studies [42, 44, 47, 50, 52, 56, 59]. Among them, five studies reported higher frequency of methylated APC in plasma/serum DNA of BC patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 29 studies, there were 26 case-control studies [12, 14, 1533, 35, 3740] and 3 cohort studies [35, 36, 41]. Interestingly, 12 studies [12, 14, 15, 18, 19, 22, 24, 26–28, 32, 38] among 26 case-control studies also did the cohort analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the results obtained in our study could be confirmed using a quantitative MSP method. However, a number of studies have suggested that MSP has a high sensitivity and specificity for the identification of breast cancer cells [21,22]. A frequency of 10-42% for the methylation of RARβ2 in the promoter region of breast cancer tissue has been reported [23].…”
Section: Discussionmentioning
confidence: 99%